Hubungan Karateristik Mahasiswa Terhadap Kemampuan Empati Mahasiswa Keperawatan: Studi Cross Sectional - Dwi Nopriyanto; Dea Tri Regina; Bahtiar Bahtiar; Syukma Rhamadani Faizal Nur; Erwan Ahmad; Iwan Samsugito; Dewi Kusumaningsih (Universitas Malahayati Lampung, 2025)
ABSTRACT Empathy plays an important role in interpersonal relationships and improves communication skills. Empathy plays an important role in providing quality care, and it is important for nursing students and the nursing profession to develop. Nursing students not only need to acquire technical skills but also have interpersonal skills. This study aims to determine the relationship between student characteristics and nursing students' empathy abilities. The research design is descriptive analytical with a Cross-Sectional approach. This study involved students of the Diploma of Nursing study program, Faculty of Medicine, Mulawarman University, semesters 2, 4, and 6 totaling 189 students using a total sampling technique. Bivariate analysis using the Chi-Square test with SPSS version 25. The results of the study explained that the majority of students had good empathy skills (61.9%), and there was no significant relationship between student characteristics such as gender, age, semester, reasons for choosing to study nursing and close friends with students' empathy skills. But parents' jobs have a significant relationship with students' empathy skills (p 0.05). The conclusion is that the findings show that nursing students have good empathy skills, but need further improvement. These results make nursing educators pay more attention to the development of empathy skills of nursing students, increasing the level of empathy is useful in improving health care standards. Keywords: Characteristics, Empathy Ability, Nursing Students ABSTRAK Empati memiliki peran penting dalam hubungan interpersonal serta meningkatkan kemampuan komunikasi. Empati memainkan peran penting dalam memberikan perawatan berkualitas, dan penting bagi mahasiswa keperawatan dan profesi keperawatan untuk dikembangkan. Mahasiswa keperawatan bukan hanya perlu memperoleh keterampilan secara teknis tetapi juga memiliki ketrampilan hubungan antar manusia. Penelitian ini bertujuan untuk mengetahui hubungan karateristik mahasiswa terhadap kemampuan empati mahasiswa keperawatan. Desaian penelitian adalah diskriptif analitik dengan pendekatan Cross-Sectional. Penelitian ini melibatkan mahasiswa prodi D3 Keperawatan Fakultas Kedokteran Universitas Mulawarman semester 2, 4, dan 6 berjumlah 189 mahasiswa dengan menggunakan teknik total sampling. Analisa bivariat menggunakan uji Chi-Square dengan SPSS versi 25. Hasil penelitian dijelaskan bahwa mayoritas mahasiswa memiliki kemampuan empati baik (61.9%), dan tidak ada hubungan yang signifikan antara karateristik mahasiswa seperti jenis kelamin, usia, semester, alasan memilih kuliah keperawatan dan teman dekat dengan kemampuan empati mahasiswa. Tetapi pekerjaan orang tua memiliki hubungan yang signifikan dengan kemampuan empati mahasiswa (p0.05). Kesimpulan mendapatkan temuan menunjukkan bahwa mahasiswa keperawatan mempunyai kemampuan empati yang baik, tetapi perlu peningkatan lebih lanjut. Hasil ini membuat pendidik keperawatan lebih memperhatikan pengembangan kemampuan empati mahasiswa keperawatan, meningkatkan tingkat empati bermanfaat dalam meningkatkan standar perawatan kesehatan. Kata Kunci: Karateristik, Kemampuan Empatik, Mahasiswa Keperawatan